2010
DOI: 10.1021/jp9106684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Charge Density and Thermal History on the Morphologies of Spontaneously Formed Unilamellar Vesicles

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Upon changing the hydrophobic tail from linear alkanes ( 2A and 2B ) to dodecanol ( 2C ) resulted in lamellar disks of diameters ranging from about 12 to 20 nm (Figure 1). Unlike spherical micelles and rod‐like micelles, disks are not frequently encountered 3, 33–40. There are only a handful of reported systems that are capable of forming disk morphology as they are found to be formed under very specific compositions and/or conditions 34–37, 39.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon changing the hydrophobic tail from linear alkanes ( 2A and 2B ) to dodecanol ( 2C ) resulted in lamellar disks of diameters ranging from about 12 to 20 nm (Figure 1). Unlike spherical micelles and rod‐like micelles, disks are not frequently encountered 3, 33–40. There are only a handful of reported systems that are capable of forming disk morphology as they are found to be formed under very specific compositions and/or conditions 34–37, 39.…”
Section: Resultsmentioning
confidence: 99%
“…Disk‐like micelles formed by lipids have been demonstrated to transform into unilamellar vesicles by Nieh and co‐workers 33–35. In their detailed studies, by using multitude of characterization techniques, they identified that by thermal treatment, bicelles transformed to vesicles and the disk‐like micelles were found to be the key intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, systems formed by long‐alkyl‐chain phospholipids and DHPC have been reported to produce reasonably monodisperse unilamellar vesicles that are thermodynamically stable, with radii ranging from 10 to 40 nm 67–70. Several kinetic studies have shown that discoidal bicelle morphology is a precursor to small‐vesicle morphology 70, 71. DHPC molecules solubilize the DMPC bilayer similar to a surfactant; however, DHPC is a phospholipid with the same polar head group as DMPC.…”
Section: Bicelle Suitability For Skin‐related Applicationsmentioning
confidence: 99%
“…In the absence of Ln 3+ , bicelles were disk-shaped in the gel phase, and chiral nematic in the liquid crystalline phase, which were described as wormlike micelles, and at higher temperatures were multilamellar vesicles [27]. Additionally, recent studies have demonstrated that inclusion of small amount of charged lipids eliminated the appearance of the worm-like or ribbon phase [31] Hereafter, the use of the term bicelle in most studies refers only to the sample composition and not to the disk-shaped morphology. A comparative study of alignable and non-alignable bicelles associated to the temperature changes of the system could be helpful to clarify the morphological transitions involved in this process.…”
Section: Dmpc/dhpc Bicellar Systemsmentioning
confidence: 99%